Peningkatan Hasil Belajar Matematika Siswa Melalui Strategi Pakem Di Kelas Viii MTs Nurul Amaliyah Tanjung Morawa - Siti Maysarah (UIN Sumatera Utara Medan, 2018)
The purpose of this research is: (1) To know the success rate of the PAKEM strategy implementation in improving students’ mathematics learning result on the material of cube and crossbar in grade VIII MTs Nurul Amaliyah Tanjung Morawa. This type of research is a classroom action research with two cycles, namely cycle I and cycle II. The results of this research is the success rate of the PAKEM strategy implementation in improving students’ mathematics learning result in grade VIII MTs Nurul Amaliyah Tanjung Morawa on the material of cube and crossbar is 68% from before action taken. With the completeness of classical learning outcomes before action taken is 20%, after action on cycle I is 72% and cycle II is 88%.